Covering for cutting acclimatization to maximizing growth and yield in Mucuna bracteata D.C. propagation - Wikka Sasvita; Bayu Pratomo; Alex Chan Siagian (Jurnal Ilmiah Pertanian, 2023)
The coverage of Mucuna bracteata D.C. cuttings plays a vital role in their survival percentage, as it helps maintain appropriate humidity and temperature levels. Uncovered cuttings may experience inhibited growth due to their inability to adapt to direct sunlight. Moreover, the acclimatization process following the removal of the cover is crucial before transferring the cuttings to the field. This research aimed to investigate the impact of various coverage durations on the survival rate of Mucuna bracteata D.C. cuttings. The research was conducted in Telaga Said Village, Langkat Regency, Indonesia, using a non-factorial randomized block design (RBD). The treatments included coverage durations of 1 week (L1), 2 weeks (L2), 3 weeks (L3), 4 weeks (L4), and 5 weeks (L5) after the initial covering of the cuttings. The results revealed that a 4-week coverage duration provided an excellent survival rate of 85% for Mucuna bracteata D.C. cuttings, along with the highest average number of leaves, number of tendrils, number of root nodules, average fresh and dry weight of the crown, average fresh and dry weight of the roots, and the highest average root-to-crown ratio. This information is valuable for the successful propagation and establishment of Mucuna bracteata D.C. cuttings, aiding in the efficient cultivation of this species. Further studies can explore additional factors that may contribute to the overall success of Mucuna bracteata D.C. propagation.